Compilation of statements of auditing standards in the Philippines : Nos. 1-12 Audit manual for commercial banks. - Auditing Standards and Practices Council ([place of publication not identified] : [publisher not identified], 1993)
The purpose of this Philippine Standard on Auditing (PSA) is to establish standards and provide guidance on the accountant's professional responsibilities when an engagement to compile financial information is undertaken and the form and content of the report the accountant issues in connection with such a compilation.
Foreword -- Preface -- No.1 The objectives, scope & responsibilities of an independent auditor in undertaking an audit -- No.2 Generally Accepted Auditing standards -- No. 3 Audit Engagement letters -- No. 4 Client representations -- No. 5 Independent Auditor's Report on audited financial statements -- No.6 Study and evaluation of the accounting systems & related internal control in connection with an audit -- No.7 Audit Evidence & Documentation -- No. 8 Control of Quality of audit work -- No. 9 Planning & Supervision -- No. 10 Audit Sampling -- No. 11 Procedures to be followed in the review of clients income, withholding & Value added tax returns -- No.12 fraud & Error.
Keywords: AUDITING -- STANDARDS